Effectiveness of Zumba Exercise on Maximum Oxygen Volume, Agility, and Muscle Power in Female Students - Puspodari Puspodari; Oce Wiriawan; Hari Setijono; Poppy Elisano Arfanda; Wasis Himawanto; Susilaturochman Hendrawan Koestanto; Budi Hantoro; Septyaning Lusianti; Rendhitya Prima Putra; Rahayu Prasetiyo; Adi Pranoto (OVS LLC, 2022)
The study purpose was to prove the effectiveness of zumba exercise on VO₂max, agility, and muscle power in students at Universitas Nusantara PGRI Kediri, East Java, Indonesia. Materials and methods. This research is a pre-experimental research design with One group Pretest-Posttest Design. A total of 15 female students from the Student Activity Unit aerobic dance exercise at Universitas Nusantara PGRI Kediri, East Java, Indonesia, aged 19-24 years, body mass index (BMI) 19.0-24.0 kg/m², normal blood pressure, resting heart rate normal, normal oxygen saturation (SpO₂), voluntarily participated in the study. Zumba exercise was carried out for 30 minutes/session with an intensity of 80% HRmax with a frequency of 3x/week for 8 weeks. The measurement of maximum oxygen volume (VO₂max) used the Multi-Stage 20-m Shuttle Run Fitness Test. The measurement of leg muscle power used the vertical jump test, while the arm muscle power was evaluated using the medicine ball throw test. Data analysis used Paired Sample t-Test with a significance level of 5%. Results. The results obtained: mean VO₂max between pretest vs post-test (26.64±4.25 vs. 30.76±4.20 mL/kg/min; p ≤ 0.001), average agility between pretest and post-test (15.76±1.24 vs. 14.55±1.27 seconds; p ≤ 0.001), average limb muscle power between pretest vs posttest (394.21±66.36 vs. 411.09±67.45 joule; p ≤ 0.001), and the average arm muscle power between pretest vs posttest (123.45±17.12 vs. 138.21±13.92 joule; p ≤ 0.001). Conclusions. Based on the results of the study, it was concluded that Zumba exercise carried out for 30 minutes/training session, with an intensity of 80% HRmax, frequency 3x/week for 8 weeks increased VO₂max, agility, and muscle power in students at Universitas Nusantara PGRI Kediri, East Java, Indonesia.